(untitled) (Tribhuvan University Journal of Microbiology, 2024)
Objectives: The study aims to assess microbial contamination in ice cream sold in Pokhara, with a specific focus on Bacillus cereus and to determine its antibiotic susceptibility pattern. Methods: The cross- sectional study was conducted on 108 ice cream samples of different brands collected from different shops in Pokhara. The samples were cultured on plate count agar for heterotrophic count and were also cultured on Mannitol Egg Yolk Polymyxin Agar for B. cereus identification. B. cereus was identified through cultural characteristics, gram staining and various biochemical tests. Antibiotic susceptibility test was performed by Kirby Bauer disc diffusion technique. Results: Heterotrophic plate count revealed 91.67% (n=99) ice-cream samples were contaminated with average count of 5.25±0.78 log CFU/gm. Open cup ice-cream samples of all nine brands showed the maximum bacterial count with average of 5.49±0.73 log CFU/gm whereas that of minimum was found in sealed cone samples (4.99±0.51 log CFU/gm). B. cereus contamination was observed in 16.67% (n=18) ice-cream samples with average count of 3.52±0.25 log CFU/gm. Out of nine brands, 5 brands were contaminated with B. cereus. Sealed cone ice cream did not show any growth of B. cereus and heterotrophic plate count was also minimum. All the isolates were susceptible toward used antibiotic except Piperacillin/Tazobactum. Conclusion: The present study reveals the occurrence of microorganism in the ice cream which is the frozen dairy product. Sealed cone ice cream is generally considered safer compared to other types.